PERINATAL OUTCOME IN SUCCESSFUL VAGINAL BIRTH AFTER CESAREAN SECTION - HAQ , W; BAWAR , R; BANO , S; GUL , F (Biological and Clinical Sciences Research Journal, 2024)
Successful vaginal birth has been reported in 60%–80% of cases reported in published studies of women attempting vaginal birth after a previous Cesarean section. The recommended criteria for selecting candidates suitable for VBAC are potentially applicable in tertiary centers in developing countries, but there are many inadequacies in meeting them in our environment. VBAC avoids major abdominal surgery, lowers the women’s risk of postpartum morbidities like fever, blood transfusion, infections, and shorter hospital stay, and encourages earlier breastfeeding and better bonding between mother and neonate. Objectives: To determine the frequency of perinatal outcomes in successful vaginal birth after cesarean section (VBAC). Methods: Descriptive, case series study in the Department of Obstetrics & Gynecology, Lady Reading Hospital, Peshawar from August 2020 to February 2021. A total of 207 pregnant women with singleton pregnancy of cephalic presentation with successful vaginal birth after cesarean of gestational age 37-41 weeks were included. Patients with multiple pregnancies, ruptured uterus, placenta previa, and fetal malpresentation were excluded. After taking informed consent, all women were followed till delivery and perinatal outcome i.e. low birth weight, Apgar score<7 at 1 minute, and NICU admission was noted. Results: The age range in this study was from 18 to 40 years with a mean age of 29.32 ± 4.57 years. The majority of the patients 104 (50.24%) were between 31 to 40 years of age. The mean gestational age was 38.33 ± 1.17 weeks. The mean parity was 2.11 ± 0.82. In my study, the frequency of perinatal outcome in successful vaginal birth after the cesarean section was as follows; low birth weight in 15.94%, APGAR score<7 at 1 minute in 9.67%, and NICU admission in 14.01% neonates. Conclusion: This study concluded that the frequency of perinatal outcome in successful vaginal birth after cesarean section was as follows; low birth weight in 15.94%, APGAR score<7 at 1 minute is 9.67%, and NICU admission in 14.01% neonates.